The Effects of a Campaign on Awareness and Participation Among Local Youth at the Lenggong Valley World Heritage Site, Malaysia. (2nd October 2015) - Jaafar, Mastura; Md Noor, Shuhaida; Rasoolimanesh, S. Mostafa
Abstract : The capacity of a United Nations Educational, Scientific and Cultural Organization (UNESCO) World Heritage Site (WHS) to sustain its designated criteria into the future is a function of how valuable local residents perceive the WHS to be, and how motivated they are to contribute toward efforts to maintain its status. In June 2012, Malaysia's Lenggong Valley became a WHS. We investigate the effectiveness of a campaign targeting young local residents to increase their awareness of the importance of preserving the heritage of Lenggong. We undertook a questionnaire — designed to assess participants' awareness of the value of the WHS and their willingness to participate in efforts to maintain the WHS — aimed at students from all three secondary schools in Lenggong before and after the campaign. In all, 175 completed questionnaires were analysed: the data revealed that the campaign had a significant effect on improving participants' awareness of the value of the WHS and on improving their willingness to participate in WHS conservation activities.